2017
DOI: 10.1016/j.drugalcdep.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between treatment accessibility and preference amongst out-of-treatment individuals who engage in non-medical prescription opioid use

Abstract: Background Relatively little is known regarding the perception of medication-assisted treatments (MATs) and other treatment options amongst individuals that engage in non-medical prescription opioid use. This study surveyed out-of-treatment individuals that misuse opioids to better understand how perceived access to treatment shapes treatment preference. Methods Participants (n=357) were out-of-treatment adults registered as workers on the Amazon Mechanical Turk platform who reported current non-medical pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“… 72 In this review, we focus on the most widely used OUD therapies, their shortcomings, and the bottlenecks to accessing them. 11 …”
Section: Current Opioid Use Disorder Therapies and Their Shortcomingsmentioning
confidence: 99%
See 2 more Smart Citations
“… 72 In this review, we focus on the most widely used OUD therapies, their shortcomings, and the bottlenecks to accessing them. 11 …”
Section: Current Opioid Use Disorder Therapies and Their Shortcomingsmentioning
confidence: 99%
“…9 , 78 , 79 There are only 1590 methadone distributers in the United States, which are highly regulated clinics that are concentrated in urban areas, creating geographical disparities in OUD treatment. 10 , 11 , 79 In addition to geographical barriers, these clinics frequently have stringent and stigmatizing compliance requirements, such as daily visits and frequent urine screenings for illicit drugs. 11 , 80 Although these barriers to treatment could potentially be addressed through concerted efforts to expand access, 40% of patients still relapse within 1 year of initiating methadone therapy.…”
Section: Current Opioid Use Disorder Therapies and Their Shortcomingsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, researchers in addiction science have also begun to utilize mTurk. These studies have spanned a diverse range of theoretical perspectives and methods including, but not limited to, behavioral economics (e.g., Bickel, Jarmolowicz, Mueller, Koffarnus, & Gatchalian, 2012;Johnson, Herrmann, & Johnson, 2015;Kaplan et al, 2017;Morris et al, 2017;Peters, Rosenberry, Schauer, O'Grady, & Johnson, 2017), tobacco control policy (e.g., Lazard et al, 2017;Pearson et al, 2016;Shi, Wang, Emery, Sheerin, & Romer, 2017), behavioral addictions (e.g., Bock et al, 2016;Gearhardt, Corbin, & Brownell, 2016), public opinion related to addiction-related policy (e.g., Huhn, Tompkins, & Dunn, 2017;Rudski, 2016;Wen, Higgins, Xie, & Epstein, 2016), and measure development (e.g., Dunn, Barrett, Herrmann et al, 2016;Dunn, Barrett, Yepez-Laubach et al, 2016;Lac & Berger, 2013). Existing evidence supports the reliability and validity of common substance use scales when used on mTurk (e.g., the Alcohol Use Disorder Identification Test [AUDIT]; Kim & Hodgins, 2017).…”
mentioning
confidence: 99%
“…Individuals engaging in non-medical opioid use who meet criteria for OUD may choose not to engage in OMT, instead preferring supervised withdrawal only, or counseling and/or 12step based mutual support groups for ongoing care. Our group recently reported that 46.2% of individuals engaging in non-medical opioid use had a negative view of OMT and/or naltrexone (Huhn, Tompkins, and Dunn, 2017). Individual motivation for treatment and conceptualization of recovery likely affects where and for how long patients may choose to engage in treatment.…”
Section: Introductionmentioning
confidence: 99%